The MultiTEP platform–based Alzheimer's disease epitope vaccine activates a broad repertoire of T helper cells in nonhuman primates. Issue 3 (24th February 2014) - Davtyan, Hayk; Ghochikyan, Anahit; Petrushina, Irina; Hovakimyan, Armine; Davtyan, Arpine; Cribbs, David H.; Agadjanyan, Michael G.
Abstract: Background: As a prelude to clinical trials we have characterized B‐ and T‐cell immune responses in macaques to AD vaccine candidates: AV‐1955 and its slightly modified version, AV‐1959 (with 3 additional promiscuous Th epitopes). Methods: T‐ and B‐cell epitope mapping was performed using the ELISPOT assay and competition ELISA, respectively. Results: AV‐1955 and AV‐1959 did not stimulate potentially harmful autoreactive T cells, but instead activated a broad but individualized repertoire of Th cells specific to the MultiTEP platform in macaques. Although both vaccines induced robust anti‐Aβ antibody responses without producing antibodies specific to Th epitopes of MultiTEP platforms, analyses of cellular immune responses in macaques demonstrated that the addition of Th epitopes in the case of AV‐1959 created a more potent, superior vaccine. Conclusion: AV‐1959 is a promising vaccine candidate capable of producing therapeutically potent anti‐amyloid antibody in a broader population of vaccinated subjects with high MHC class II gene polymorphisms.